The Effect of Whatsapp Video-Based Education About Childbirth on the Knowledge and Attitudes of Third Trimester Pregnant Women - Eni Sulastri; Sri Linda; Triany L. Pelu (Poltekkes Kemenkes Semarang, 2021)
Background: One of efforts to reduce maternal and child mortality is childbirth assistance by health workers. In reality in the field the community do not fully trust health workers as childbirth helpers, they prefer traditional birth attendance as childbirth helpers. There is still childbirth assistance by non-health workers (traditional birth attendance), therefore the provision of communication, information and education (CIE) must still be provided in various ways including through social media, one of them is Whatsapp. Health counseling through video media has advantages in terms of providing good visualization to facilitate the process of knowledge absorptionMethods: This study is a Quasy Experimental, it use one-group pretest posttest design. Research took place in the working area of Kalumpang Community Health Center, Ternate city. The study sample included 31 pregnant women who met the inclusion criteria. Data analysis using SPSS statistics version 25 with a paired sample t testResults: The results of that study there is an increase in knowledge from pretest to posttest after being given educational intervention through whatsapp video about childbirth, with a p-value = 0.000. There was an increase in attitude after being given educational intervention through whatsapp video about childbirth (p-value = 0.000).Conclusion: The provision of whatsapp video-based education becomes an alternative and successful in providing health information (preparation for childbirth).